IFALD in children: What's new? A narrative review - Di Dato, Fabiola; Iorio, Raffaele; Spagnuolo, Maria Immacolata (Frontiers in Nutrition, 2022)
Abstract: Intestinal Failure Associated Liver Disease (IFALD) is a progressive liver disease complicating intestinal failure (IF). It is a preventable and reversible condition, but, at the same time a potential cause of liver cirrhosis and an indication to combined or non-combined liver and small bowel transplantation. The diagnostic criteria are not yet standardized so that its prevalence widely varies in literature. Pathophysiology seems to be multifactorial, related to different aspects of intestinal failure and not only to the long-term parenteral nutrition treatment. The survival rates of children with IF have increased so that the main problems today are preventing complications and ensuring a good quality of life. IFALD is one of the most important factors limiting long-term survival of patients with IF. For this reason, more and more interest is developing around it and the number of published articles is increasing rapidly. The purpose of this narrative review is to focus on the main aspects of the aetiology, pathophysiology, management, prevention and treatment of IFALD, based on what has been published mainly in the last 10 years. Controversies and current research gaps will be highlighted with the aim to pave the way for new project and high-quality clinical trials.